2014
DOI: 10.1002/jcu.22201
|View full text |Cite
|
Sign up to set email alerts
|

Determination of steroid injection sites using lidocaine test in adhesive capsulitis: A prospective randomized clinical trial

Abstract: We found that subacromial lidocaine injection prior to steroid injection resulted in better improvement of pain than conventional GH injection for patients with adhesive capsulitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Some clinical trials have reported that corticosteroid injection into the SA bursa had an effect similar to that of IA injection in the treatment of idiopathic FS. [ 13 15 ] These results suggested that the SA bursa may be a potential pathologic lesion in idiopathic FS. However, there is no clear explanation as to whether the SA bursa is a major or minor clinical lesion.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Some clinical trials have reported that corticosteroid injection into the SA bursa had an effect similar to that of IA injection in the treatment of idiopathic FS. [ 13 15 ] These results suggested that the SA bursa may be a potential pathologic lesion in idiopathic FS. However, there is no clear explanation as to whether the SA bursa is a major or minor clinical lesion.…”
Section: Discussionmentioning
confidence: 84%
“…[ 13 , 14 ] With injection of 40 mg of triamcinolone and 2 mL 2% lidocaine, Kim et al found RI injection was superior to IA in the early phase of FS. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…Majority of literature of bipartite patella is based on single case reports and small case series. Furthermore, the use of lidocaine blocks is not new to orthopedic surgeons and has been using them since years dependably without any major issues 1213…”
Section: Discussionmentioning
confidence: 99%
“…Лучшие результаты лечения получены у больных с четкими ультрасонографическими данными субакромиального бурсита [43]. Сравнение изо-лированного введения ГКС и сочетания их с местными анестетиками продемонстрировало более быстрое купи-рование боли при комбинированной терапии у 92 паци-ентов с адгезивным капсулитом [45].…”
Section: таблицаunclassified